The lady of Galway Manor - Deibel, Jennifer, 1978- (Revell, a division of Baker Publishing Group, 2022)
"In 1920 Galway, amid the Irish War of Independence, the daughter of a British landlord becomes an apprentice jeweler to the descendent of the creator of the famed Claddagh ring. As the two learn to work together and see each other in a new light, they start to uncover the true meaning of love, loyalty, and friendship"--